The Role of Service Quality in Strengthening the Influence of Service Rates and Facilities on Transaction Decisions: A Study of BRILink Agents in Pesantren Village, Kediri - Chandra Kurniawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of service rates and facilities on people's transaction decisions with service quality as a moderating variable at BRILink Agents in Pesantren Village, Kediri City. This study was motivated by the phenomenon of several BRILink agents that are close to each other and offer different service rates and facilities, thus creating competition and influencing people's decisions in choosing an agent. The research approach used is quantitative with a survey method through a questionnaire to 97 respondents who are BRILink agent users. The data analysis technique uses multiple linear regression tests to determine the direct influence and the influence moderated by service quality. The results of the study show that service rates and facilities have a positive and significant effect on transaction decisions. In addition, service quality has been proven to be able to strengthen the influence of service rates and facilities on people's decisions in making transactions. This emphasizes the importance of a combination of competitive tariff determination, provision of adequate facilities, and quality service in improving transaction decisions for BRILink agent users.